Monte Carlo simulation in communication system / Mazlina Poniran - Poniran, Mazlina (2009)
Monte Carlo simulations are used to evaluate the bit error rate (BER) due to the degrading effects in a communication system. The communication system to be studied consists of binary PSK modulation with both signal points in the signal constellation lying in the direct (in-phase) channel. The filter at the output of the modulator is a third-order Butterworth filter with a bandwidth equal to the bit rate ( BW = rb ), leads to intersymbol interference (ISI). The filter of the output must continuous from block to block. This is accomplished by using the initial condition parameter that provided in filter and the value of delay must be choosing correctly in this system. Simulation result will be compared with the ideal (zero ISI) result in order to determine the increase in BER resulting from the filter - induced ISI.